2018
DOI: 10.2136/vzj2018.05.0099
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Surface and Subsurface Water Balance Changes Due to Burn Severity

Abstract: Core Ideas Burn severity data informed a hydrologic model to assess water balance changes. Loss of vegetation and evapotranspiration exceeded impact of increased runoff. High burn severity may cause drier site conditions due to increased runoff. Change in evapotranspiration acts at long timescales while runoff is event based. Forest fires have a significant impact on hydrology, such as reduced infiltration rates leading to increased flooding. However, post‐fire water balance changes and the competing hydrolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 100 publications
1
36
1
Order By: Relevance
“…Our results agree with previous studies showing that ET decreases after a fire event (e.g. [9,89] in semi-arid; [15,90] in boreal forests; and [13,35,91] in temperate conifer forests). In Mediterranean ecosystem, Sánchez et al [17] studied the temporal evolution of changes insurface energy balance over an eleven-year period following fire in a maritime pine-shrub mixed forest (Spain).…”
Section: How Does Fire Modify Et Lst Lsa Ndvi and Nbr?supporting
confidence: 93%
See 2 more Smart Citations
“…Our results agree with previous studies showing that ET decreases after a fire event (e.g. [9,89] in semi-arid; [15,90] in boreal forests; and [13,35,91] in temperate conifer forests). In Mediterranean ecosystem, Sánchez et al [17] studied the temporal evolution of changes insurface energy balance over an eleven-year period following fire in a maritime pine-shrub mixed forest (Spain).…”
Section: How Does Fire Modify Et Lst Lsa Ndvi and Nbr?supporting
confidence: 93%
“…However, forested areas affected by high burn severity show a decrease in soil moisture. In this case, the increase in surface runoff exceeds the reduction in ET and leads to drier post-fire soils [9,12]. Post-fire changes in vegetation, soil and water balance corroborate wildfires impact on energy balance [13][14][15].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Numerical modeling experiments also showed that roughness parameter values varied with spatial scale, which has implications for the transferability of calibrated roughness parameters to other sites. Since the hydrologic processes in burned basins have been altered and there may be limited time to gather information prior to the onset of rainfall, it is not uncommon for post-fire modeling efforts to estimate hydraulic roughness based on values previously calibrated at other burned sites (Istanbulluoglu and Bras, 2005;Cydzik and Hogue, 2009;Wagenbrenner et al, 2010;Atchley et al, 2018;McGuire et al, 2018). Numerical experiment 1 showed that the best-fit effective Manning n eff values for the entire watershed decreased as a power-law function of drainage area (a proxy for flow discharge).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of the appropriate timescale is an important aspect to consider in vegetation disturbance studies. For example, research focused on forest disturbance over a single summer season, such as post-fire hydrology in New Mexico shows that surface runoff and recharge both rise following fire (Atchley et al, 2018). However, these studies do not measure the year-long change in water balance, which is critical for snow-driven systems.…”
Section: Introductionmentioning
confidence: 99%